Risk stratification of patients with cardiac sarcoidosis: the ILLUMINATE-CS registry . (29th June 2022) - Nabeta, Takeru; Kitai, Takeshi; Naruse, Yoshihisa; Taniguchi, Tatsunori; Yoshioka, Kenji; Tanaka, Hidekazu; Okumura, Takahiro; Sato, Shuntaro; Baba, Yuichi; Kida, Keisuke; Tamaki, Yodo; Matsumoto, Shingo; et al.
Abstract: Aims: This study evaluated the prognosis and prognostic factors of patients with cardiac sarcoidosis (CS), an underdiagnosed disease. Methods and results: Patients from a retrospective multicentre registry, diagnosed with CS between 2001 and 2017 based on the 2016 Japanese Circulation Society or 2014 Heart Rhythm Society criteria, were included. The primary endpoint was a composite of all-cause death, hospitalization for heart failure, and documented fatal ventricular arrhythmia events (FVAE), each constituting exploratory endpoints. Among 512 registered patients, 148 combined events (56 heart failure hospitalizations, 99 documented FVAE, and 49 all-cause deaths) were observed during a median follow-up of 1042 (interquartile range: 518–1917) days. The 10-year estimated event rates for the primary endpoint, all-cause death, heart failure hospitalizations, and FVAE were 48.1, 18.0, 21.1, and 31.9%, respectively. On multivariable Cox regression, a history of ventricular tachycardia (VT) or fibrillation [hazard ratio (HR) 2.53, 95% confidence interval (CI) 1.59–4.00, P < 0.001], log-transformed brain natriuretic peptide (BNP) levels (HR 1.28, 95% CI 1.07–1.53, P = 0.008), left ventricular ejection fraction (LVEF) (HR 0.94 per 5% increase, 95% CI 0.88–1.00, P = 0.046), and post-diagnosis radiofrequency ablation for VT (HR 2.65, 95% CI 1.02–6.86, P = 0.045) independently predicted the primary endpoint. Conclusion: Although mortality is relatively low in CS, adverse events are common, mainly due to FVAE. Patients with low LVEF, with high BNP levels, with VT/fibrillation history, and requiring ablation to treat VT are at high risk. Structured Graphical Abstract: Structured Graphical Abstract Clinical characteristics, findings on cardiovascular imaging, prognosis, and prognostic factors in patients with cardiac sarcoidosis: summary results of ILLUMINATE-CS.